Functional Porous Organic Polymers with Conjugated Triaryl Triazine as the Core for Superfast Adsorption Removal of Organic Dyes - Zhang, Yong; Hong, Xin; Cao, Xiao-Mei; Huang, Xiao-Qing; Hu, Bing; Ding, San-Yuan; Lin, Hui (ACS applied materials & interfaces, 2021)
Developing efficient adsorbents for the removal of water pollutants is of great significance for environmental protection. In this study, conjugated triaryl triazines (CTT), containing intramolecular hydrogen-bonding patterns, were recognized to be intriguing building blocks for the construction of porous organic polymer (POP) adsorbents. These planar monomers with multiple phenolic hydroxyl groups facilitated the formation of aza-linked polymers with hierarchical porous structures, sheet-like morphology, good surface wettability, and high degree of functionality. Such structural characteristics of the CTT-POP adsorbents provided superfast adsorption of various cationic dyes from water. For the adsorption of methylene blue dye, the pseudo-second-order rate constant of CTT-POP-1 is 12.9 g mg–1 min–1, superior to those reported in the existing literature. In addition, CTT-POP-1 can be regenerated at least seven times with no loss in performance, indicating its potential application in water treatment.